Microwave bandpass filter at digital applications / Nirna Fairuzati Jamehari - Jamehari, Nirna Fairuzati (2010)
This paper presents a microwave single layer combline bandpass filter structured with a co planar waveguide. It is designed to be operated at digital broadcasting frequency spectrum. This microstrip filter is designed and simulated using CST Microwave design software. When the specifications met, the circuit is fabricated on FR-4 substrate and measured using Vector Network Analyzer, VNA. The results are then compared and analyzed.